Makna Frase ἐν Χριστῷ (dalam Kristus) sebagai Dasar Spiritualitas dan Kepemimpinan Paulus dalam 1 Korintus 4: 6-21 - Andhika, Leonardus; Aryanto, Antonius Galih Arga Wiwin (Media: Jurnal Filsafat dan Teologi, 2025)
This study aims to explore the theological meaning of the phrase ἐν Χριστῷ (“in Christ”) in 1 Corinthians 4:6–21 as the foundation of Paul’s spirituality and leadership. Employing a historical-critical approach and lexical analysis, it investigates the intimate relationship between Paul and Christ and its implications for the Corinthian community. The findings reveal that Paul’s spiritual experience in Damascus signified a life transformation and unity with Christ, which shaped his leadership style and teaching pattern. The phrase ἐν Χριστῷ is understood not merely as a theological concept but as a practical principle underlying Paul’s humble, participatory, and unifying leadership. In the context of a divided Corinthian church, leadership “in Christ” emerges as a pastoral model that educates and unites through apostolic example. This study concludes that the spirituality of ἐν Χριστῷ provides the foundation for forming a faith community living in unity with Christ and with one another and offers an ecclesial leadership model grounded in love, humility, and exemplary service.